Formations of Belief: Historical Approaches to Religion and the Secular - Guenther, Katja; Weiss, Max; Nord, Philip; Grafton, Anthony; Gregory, Brad S.; Pizzigoni, Caterina; Guenther, Katja; Weiss, Max; Zaman, Muhammad Qasim; Gordon, Peter E.; Nord, Philip; Brown, Peter; et al. (Publications in Partnership with the Shelby Cullom Davis Center at Princeton University, 2019)
For decades, scholars and public intellectuals have been predicting the demise of religion in the face of secularization. Yet religion is undergoing an unprecedented resurgence in modern life—and secularization no longer appears so inevitable. Formations of Belief brings together many of today's leading historians to shed critical light on secularism's origins, its present crisis, and whether it is as antithetical to religion as it is so often made out to be.Formations of Belief offers a more nuanced understanding of the origins of secularist thought, demonstrating how Reformed Christianity and the Enlightenment were not the sole vessels of a worldview based on rationalism and individual autonomy. Taking readers from late antiquity to the contemporary era, the contributors show how secularism itself can be a form of belief and yet how its crisis today has been brought on by its apparent incapacity to satisfy people's spiritual needs. They explore the rise of the humanistic study of religion in Europe, Jewish messianism, atheism and last rites in the Soviet Union, the cult of the saints in colonial Mexico, religious minorities and Islamic identity in Pakistan, the neuroscience of religion, and more.Based on the Shelby Cullom Davis Center Seminars at Princeton University, this incisive book features illuminating essays by Peter Brown, Yaacob Dweck, Peter E. Gordon, Anthony Grafton, Brad S. Gregory, Stefania Pastore, Caterina Pizzigoni, Victoria Smolkin, Max Weiss, and Muhammad Qasim Zaman